To what extent does smoking affect gingival bleeding response to supragingival plaque? Site‐specific analyses in a population‐based study - Holde, Gro Eirin; Birgitta, Jönsson; Oscarson, Nils; Müller, Hans-Peter (Journal of Periodontal Research, 2019)
Background and objective - The aim of this study was to investigate the influence of smoking on the site‐specific association between bleeding on gingival probing and supragingival plaque and to assess whether this differs in different regions of the dentition. Methods - Data from a representative sample of 1911 adults (20‐79 years old) in Northern Norway were analyzed. Periodontal examinations consisted of full‐mouth recordings of periodontal probing depth (PD), bleeding on probing (BOP), and presence of supragingival plaque. Smoking status and background characteristics were self‐reported by questionnaire. The association between plaque and BOP was assessed in several three‐level (subject, tooth, and site) random intercept logistic regression models adjusted for PD, smoking status, socioeconomic factors, and body mass index. In a further model, it was assessed whether the association between supragingival plaque and BOP differed in different parts of the dentition. Results - For plaque‐free sites, bleeding tendency was lower in smokers, the odds ratio (OR) was 0.773 with a 95% confidence interval of 0.678‐0.881 as compared to non‐smokers (OR: 1; ref., P < .001). The odds of BOP at plaque‐covered sites in non‐smokers were increased twofold (OR: 2.117; 2.059‐2.177). Albeit bleeding tendency was slightly increased in plaque‐covered sites in smokers, it was considerably lower as compared to plaque‐covered sites in non‐smokers (OR: 1.459; 1.282‐1.662, P < .001). Smoking ≥ 20 pack‐years further attenuated the association. In smokers, the odds of BOP were reduced in all parts of the dentition, lower and upper anterior and posterior teeth (χ 2 (4) = 32.043, P < .001). When restricting the data to younger adults (20‐34 year old), smoking had only a slight effect on the association between plaque and BOP. For plaque‐free and plaque‐covered sites, differences in ORs were not statistically noticeable ( P = .221 and P = .235, respectively). Conclusions - Smoking considerably attenuates the site‐specific ...